PKM Legal Counseling about the Dangers of Drugs for the Youth Generation - Sofian Syaiful Rizal; Roibin Roibin; Fakhruddin Syarief (GUYUB: Journal of Community Engagement, 2023)
The drug problem in Indonesia is still something that is urgent and complex. In the last decade, this problem has become widespread. Evidenced by the significant increase in the number of drug abusers or addicts, along with the increased disclosure of drug crime cases, the pattern of which is increasingly diverse, and the syndicated network is getting more massive. The Indonesian people, and even the world community, in general, are currently facing a very worrying situation due to the widespread illegal use of various types of drugs. This concern is getting sharpened due to the rampant illicit trafficking of narcotics which has spread to all levels of society, including among the younger generation. This will greatly affect the life of the nation and state in the future. The behaviour of some teenagers who have clearly ignored the values, norms and laws that apply in people's lives is one of the causes of the rise of drug use among the younger generation. In everyday life in the midst of society, there are still many teenagers who still abuse drugs. The method used in this dedication is a qualitative method through counselling by explaining clearly and comprehensively the Dangers of Drug Abuse for the Young Generation from a legal perspective. It is hoped that all counselling participants at Madrasah Aliyah Bustanul Faizin Besuki, Situbondo Regency, can understand and know that anything that is categorized as a type of drug is very dangerous for the younger generation